ECONOMETRIC DYNAMIC INVESTMENT MODEL ON THE EXAMPLE OF THE DATA OF THE REPUBLIC OF KAZAKHSTAN - Babich, В. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article examines the analysis of one of the most significant macroeconomic categories that affect the country's economic growth - gross investment. The author, on the basis of statistical information for the period 1993-2020, determines the dependence of current investments on investments of the previous period and the growth rate of real gross domestic product. An autoregressive dynamic model is considered. A regression equation is constructed that gives estimates of the nonlinear investment function. For the construction, the author uses the method of partial correction, which eliminates such a problem as the bias of the estimates obtained. Key words: economic model, macroeconomics, economic growth, investment, autoregressive dynamic model, multicollinearity, analysis of variance, hypothesis testing.